Enhancing Cultural Competence in Art Education through Intercultural Dialogue - Esanova Lobar Kulmurotovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores strategies for fostering cultural competence in students through intercultural dialogue in art education. It emphasizes the importance of integrating cross-cultural perspectives, reflective practices, and collaborative learning activities. The study highlights how visual arts can serve as a platform for understanding cultural diversity, promoting social awareness, and developing professional and ethical competencies in future art educators.